THE STRATEGY OF IMPLIED MEANING FOR CREATING ROMANTIC MOMENTS BASED ON YES MAN MOVIE - Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
The movie "Yes Man" combines both romance and comedy genres, creating an enjoyable and exciting experience for viewers during romantic scenes. This research examines the various implicatures utilized in romantic scenarios in the movie and how they relate to the romantic atmosphere. The author seeks to understand the advantages of implicature within a romantic setting and has employed a qualitative research approach. The data is analyzed by exploring the dialogues' semantic meaning, maxims, context, and implicatures. The author presents two main conclusions. Implicatures that create a romantic atmosphere can be formed by either following all maxims straightforwardly or breaching some maxims. Speakers who adhere to all maxims allow the cooperative principle to function effectively. The writer notes that no implicatures breached the quality maxim, which may be because the speakers want to establish trust with the listeners first to strengthen their relationship. Secondly, the author highlights the benefits of implicatures in romantic situations. Implicatures can be used to demonstrate respect, exception, surprise, and emphasize feelings towards others. Additionally, implicatures can be used to test the emotions of the targets.